IMPLEMENTASI KEBIJAKAN PENERTIBAN PEDAGANG KAKI LIMA DI PASAR JOHAR KOTA SEMARANG - Danar Wahyu Purbo P; Ahmad Taufiq; Nunik Retno H (Journal of Politic and Government Studies, 2015)
The implementation of the street vendors’ regulation policy in Johar Market, Semarang is a policy regulated by the government that is the Local Regulation No. 11 (2000) on regulating and fostering more street vendors carried out in depth. The understanding of the traders regarding the layout of the city is absolutely necessary. Thus, to solve the street vendors’ problems in Johar Market in Semarang is not only from the government, but also made up of the participation of the people in Semarang.This is a qualitative study with the main purpose to describe in depth the implementation of the street vendors’ regulation policy in Johar Market, Semarang. This uses deep interview, documentation and analysis of documents technique in collecting the data. The data analysis in this study includes data reduction, data presentation, and data verification stage or conclusion.It can be concluded that the implementation of the street vendors’ regulation policy in Johar Market, Semarang has run optimally in the implementation. Department of the Municipal Market Semarang and Semarang municipal police and its related agencies have been monitoring and regulating the street vendors in Johar Market, Semarang properly and according to the procedure. The socialization of the implementation of the street vendors’ regulation policy in Johar Market, Semarang has been submitted through the coordination meeting by the related government institutions to the people, especially for the street vendors in Johar market, Semarang.Nevertheless, there are still some deficiencies such as; the quantity and quality of human resources that need to be improved; lack of resources methods (the work without Standard Operating Procedures is still a lot). The characteristics of the implementing organization, policy environment like social and economic, political, public support and cultural community provides an enormous influence on the success of the implementation of the street vendors’ regulation policy in Johar Market, Semarang. Keywords: implementation; regulation; street vendor